Answer:
0
Step-by-step explanation:
hi
Answer:
g(f(x))=x^2 + 14x + 48
Step-by-step explanation:
you insert (x+7) into every x in the g(x) equation, so g(x)=(x+7)^2 - 1. then you simplify it by doing (x+7)(x+7) which gets you x^2 + 14x + 49. then you subtract the 1 from the equation to get g(f(x))=x^2 + 14x + 48.
- One number is six more than a second number.
- four times the first is 10 less than 6 times the second.⠀⠀⠀⠀
⠀⠀⠀⠀
In questions given,One number is six more than a second number.
if second number is a
first number is a+6.
and,
four times the first is 10 less than 6 times the second.
So,
4×(a+6)=6a-10
we have to solve this.
we,get our second number =a=17.
So,
first number =a+6=17+6=23
Answer: 20
Step-by-step explanation: see screenshot